2016
DOI: 10.1002/hc.21323
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of E,E‐bis(3‐bromo‐1‐chloro‐1‐propen‐2‐yl) chalcogenides and use of E,E‐bis(3‐bromo‐1‐chloro‐1‐propen‐2‐yl)sulfone in heterocyclization with primary amines

Abstract: Oxidation of E,E‐bis(3‐bromo‐1‐chloro‐1‐propen‐2‐yl) sulfide and selenide with hydrogen peroxide in chloroform/acetic acid or acetic acid affords previously unknown E,E‐bis(3‐bromo‐1‐chloro‐1‐propen‐2‐yl) sulfoxide, selenoxide, and sulfone. The reaction of E,E‐bis(3‐bromo‐1‐chloro‐1‐propen‐2‐yl) sulfone with primary amines in ethanol in the presence of NaHCO3 or Na2CO3 is found to lead not only to heterocyclization but also to alcoholysis of the chloromethylidene groups in the intermediate bis(chloromethyliden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In particular, organyl‐2‐chlorovinyl sulfoxides and sulfones easily give the substitution products with retention of the parent substrate configuration upon interaction with organylthiolates and selenolates . We have found that in the reaction of bis[(1 E )‐3‐bromo‐1‐chloro‐1‐propen‐2‐yl] sulfone with primary amines in ethanol in the presence of NaHCO 3 or Na 2 CO 3 , heterocyclization is followed by the substitution with ethoxide ion of the chlorine atoms in chloromethylidene groups of the thiomorpholine 1,1‐dioxide formed as the intermediate product to afford bis‐ethoxymethylidene derivatives of thiomorpholine 1,1‐dioxides …”
Section: Introductionmentioning
confidence: 99%
“…In particular, organyl‐2‐chlorovinyl sulfoxides and sulfones easily give the substitution products with retention of the parent substrate configuration upon interaction with organylthiolates and selenolates . We have found that in the reaction of bis[(1 E )‐3‐bromo‐1‐chloro‐1‐propen‐2‐yl] sulfone with primary amines in ethanol in the presence of NaHCO 3 or Na 2 CO 3 , heterocyclization is followed by the substitution with ethoxide ion of the chlorine atoms in chloromethylidene groups of the thiomorpholine 1,1‐dioxide formed as the intermediate product to afford bis‐ethoxymethylidene derivatives of thiomorpholine 1,1‐dioxides …”
Section: Introductionmentioning
confidence: 99%